Clinical Course of Methicillin Resistant Staphylococcus aureus in Pediatric Patients - Segundo Moisés San Lucas Coque; Sareli Anahi Aguilar Armendariz; Juan Diego Galarza López (Medisur)
Methicillin-resistant Staphylococcus aureus is a pathogen that has been noted over the years due to the increasing number of cases in pediatric patients, with community infectious origin. The number of clinical cases since 2018 has been increasing progressively to the present, which is worrying due to its consequences in the future. The treatment is mainly based on Vancomycin, Clindamycin and Linezolid, obtaining mostly positive results, however, the bioavailability of the drug in the focus of the infection and the age of the patient makes the use of these antibiotics difficult. This work analyzes 6 relevant studies for presenting a community infectious origin, patient age, treatment and the impact of signs and symptoms in contrast to mortality presented in the last 5 years to obtain an updated view of the course of the disease and the considerations therapeutic. The limitation of the spread of the infection is denoted mainly by hygiene control. Therefore, the implementation of good hygienic habits in hospitals and childcare centers can prevent infectious diseases caused by opportunistic pathogenic microorganisms.